(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objective: This study aimed to assess the psychological well-being of parents of children with Developmental Dysplasia of the Hip (DDH) and the impact of anxiety, depression, and mental health on families during and after treatment. Methodology: Fifty parents from pediatric orthopedic clinics were included, focusing on those whose children were diagnosed with DDH within the past year and had no severe comorbidities. Psychological distress was measured using the General Health Questionnaire (GHQ-28), State-Trait Anxiety Inventory (STAI), and Beck Depression Inventory (BDI). Data were collected at diagnosis and six months into treatment. Statistical analyses, including paired sample t-tests and regression, were used to track changes and identify predictors. Results: Parents experienced significant improvement in mental health during treatment. GHQ-28 scores decreased from 22.70 at diagnosis to 19.24 post-treatment, reflecting reduced psychological distress. State and trait anxiety (STAI) scores also declined significantly, from 23.34 to 19.60 and 21.66 to 18.62, respectively. BDI scores dropped from 14.28 to 11.20, indicating fewer depressive symptoms. Follow-up analyses confirmed significant improvement across all psychological measures, particularly in GHQ-28 and state anxiety. These changes were independent of socioeconomic status. Conclusion: While the initial diagnosis and treatment of DDH elevate psychological distress among parents, mental health improves over time. This underscores the need for targeted psychological support and interventions for parents throughout their child’s treatment journey.